Neuronal Regulation of Neuroprotective Microglial Apolipoprotein E Secretion in Rat In Vitro Models of Brain Pathophysiology. Issue 8 (August 2015) - Polazzi, Elisabetta; Mengoni, Ilaria; Peña-Altamira, Emiliano; Massenzio, Francesca; Virgili, Marco; Petralla, Sabrina; Monti, Barbara
<x xml:space="preserve">Abstract</x> Abstract Apolipoprotein E (ApoE) is mainly secreted by glial cells and is involved in many brain functions, including neuronal plasticity, β-amyloid clearance, and neuroprotection. Microglia—the main immune cells of the brain—are one source of ApoE, but little is known about the physiologic regulation of microglial ApoE secretion by neurons and whether this release changes under inflammatory or neurodegenerative conditions. Using rat primary neural cell cultures, we show that microglia release ApoE through a Golgi-mediated secretion pathway and that ApoE progressively accumulates in neuroprotective microglia-conditioned medium. This constitutive ApoE release is negatively affected by microglial activation both with lipopolysaccharide and with ATP. Microglial ApoE release is stimulated by neuron-conditioned media and under coculture conditions. Neuron-stimulated microglial ApoE release is mediated by serine and glutamate through N-methyl-D-aspartate receptors and is differently regulated by activation states (i.e. lipopolysaccharide vs ATP) and by 6-hydroxydopamine. Microglial ApoE silencing abrogated protection of cerebellar granule neurons against 6-hydroxydopamine toxicity in cocultures, indicating that microglial ApoE release is neuroprotective. Our findings shed light on the reciprocal cross-talk between neurons and microglia that is crucial for normal brain functions. They also open the way for the identification of possible pharmacologic targets that can modulate neuroprotective microglial ApoE release under pathologic conditions.